Key Audit Matters, Audit Delay, Earning Management, dan Kualitas Audit: A Systematic Review - Devi Nurcahya; Rizdina Azmiyanti (Economics and Business Faculty UNUSIA, 2025)
This study aims to review previous literature on the impact of KAM implementation on Audit Delay, Earning Management, and Audit Quality. The method used is a systematic literature review, with articles obtained through the Publish or Perish application. The article criteria are articles indexed by SINTA and Scopus published in 2022-2025. The results of the study indicate that disclosure of Key Audit Matters can improve the quality of financial report communication and transparency so that it has a negative effect on audit delay, and can reduce the potential for earnings management. Disclosure of Key Audit Matters also shows a positive effect on audit quality because of broader disclosure, information asymmetry between stakeholders and management can be overcome